2015
DOI: 10.1118/1.4934369
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study: Selection of a personalized radiotherapy fractionation schedule using spatiotemporal optimization

Abstract: Spatiotemporal optimization of patient plans has the potential to significantly improve local tumor control (larger BED/EUD) of patients with a favorable geometry, such as smaller tumors with larger distances between the tumor target and nearby OAR. In patients with a less favorable geometry and for fast growing tumors, plans optimized using spatiotemporal optimization and conventional (spatial-only) optimization are equivalent (negligible differences in tumor BED/EUD). However, spatiotemporal optimization yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…As a result, the findings were evaluated in a qualitative manner. 19 relevant publications were identified (Figure1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Search Strategy Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the findings were evaluated in a qualitative manner. 19 relevant publications were identified (Figure1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Search Strategy Methodologymentioning
confidence: 99%
“…Nine studies [24][25][26][27][28][29][30][31][32] were identified that outlined novel concepts which may prove to be a future basis for personalised RT prescriptions, findings are summarised in Table 3. These studies can be broadly categorised depending on the patient specific feature they are utilising as a basis for personalisation.…”
Section: Future Directions Of Personalised Radiotherapy Prescriptionsmentioning
confidence: 99%
“…These algorithms can also include objectives to be maximized, such as tumor size or cell kill . Groups have already demonstrated the feasibility of implementing spatial optimization of dose using multi-objective evolutionary algorithm methods into a clinical workflow (Kim et al 2015;Smith et al 2016). The incorporation of patient-specific tumor growth and response models into this paradigm is a reasonable goal.…”
Section: Spatial Dose and Fractionation Optimizationmentioning
confidence: 99%
“…By incorporating tumor characteristics and calculated relative dose between tumor and OAR for each patient into FSO, it is possible to optimize fractionation schedules that lead to the maximum tumor BED for each patient. 7 Radiation oncology, in line with the rest of medicine, is moving toward evidence-based, personalized therapy. 8 The ultimate goal of radiotherapy is to allow patients to have longer and healthier lives.…”
Section: Opening Statementmentioning
confidence: 99%